Assessing the Use of Artocarpus heterophyllus Seed Powder at Household Level to Treat Spring Water - Richard Rwabuto Akankwasa (Uganda Christian University, 2025)
Access to clean water remains a major challenge for the rural Ugandan communities like Nakonge, where springs are the main water source. This study explores the use of jackfruit (Artocarpus heterophyllus) seed powder and its lectin component as a natural coagulant to treat contaminated spring water at the house hold level. Water from Nakonge spring, Nsanja spring, and Bwanga community well showed high levels of E. coli and coliforms. Exceeding WHO standards. Physicochemical and microbiological tests during wet and dry seasons revealed serious contamination, especially in Bwanga. Jackfruit seeds were processed into fine powder, and jar tests were used to determine optimal dosage and performance compared to alum. Results showed that jackfruit seed powder effectively reduced turbidity and microbial counts, particularly with finer particles and proper concentrations. Lectins in the seeds also contribute antimicrobial action by disrupting microbial cells and inhibiting bacterial communication. Though not perfect, the method improved water quality significantly. This study highlights a sustainable, low-cost solution for rural households and recommends further research into improving extraction methods for even better results.
Undergraduate